The Attitude towards Olympism Values of Pupils in Schools Implementing and Not Implementing Integrated Olympic Education - Saulius Šukys; Daiva Majauskienė (Lithuanian Sports University, 2018)
Research backround and hypothesis. The research focuses on school pupils' attitudes towards Olympism values and Olympic education. We hypothesised that in schools implementing integrated Olympic education programme, pupils more associated human values with Olympism than pupils in schools where this education programme was not implemented. Research aim was to ascertain the attitude towards Olympism values of pupils in schools implementing and not implementing integrated Olympic education. Research methods. The sample included 2335 (1095 males and 1240 females) young adolescents between the ages of 13 and 18 years. Pupils' attitudes towards Olympism values were determined using the Olympic Questionnaire  (Telama et al., 2002). Research  results.  Research  results  revealed  statistically  significant  differences  towards  human  values  of Olympism (p < 0.001) and social virtues of Olympism (p < 0.001) of pupils depending on applied Olympic education programme in schools. Discussion  and  conclusions.  Our  study  revealed  that  pupils  at  schools  implementing  Integrated  Olympic Education Programme more often emphasized the importance of human and social values of Olympism compared to pupils from schools not implementing this programme. The similar differences were found when assessing the results separately for girls. Research results did not reveal differences among 13-14-year-old pupils. However, the differences were established comparing the data of older pupils. Older pupils in schools with integrated Olympic education programme more emphasized the social virtues of Olympism and the human values of Olympism. Keywords:  Olympism, attitudes towards values, Olympic education.